Comparison of 2 doses of 1% 2-chloroprocaine as spinal anesthetic for perineal and lower-limb surgeries - Kumrawat, Purva; Vanjare, Hemant; SR, Rajesh; Shankarnarayana P,; Jitendra Singh Zilwe, (Asian Journal of Medical Sciences, 2024)
Background: Spinal anesthesia is a commonly employed anesthetic technique for infraumbilical surgeries. Some of its properties may limit its use for ambulatory surgery. For outpatient surgery, lignocaine was anesthetic of choice for years, but its use has been associated with significant risk. Short-acting local anesthetic may therefore represent a valid alternative in this setting. Aims and Objectives: We compare the duration of action of sensory and motor block with 40 mg and 50 mg preservative-free 1% 2-chloroprocaine (2-CP), as a subarachnoid block. Materials and Methods: Patients posted for surgery were randomized to two groups A and B with 64 patients in each group to whom, 40 mg and 50 mg preservative-free 1% 2-CP was administered as spinal anesthesia, respectively. After completion of spinal injection onset time, evolution of sensory and motor block and vitals were studied. Results: The median onset time was 4 min for both 40 mg and 50 mg 1% 2-CP. The duration of sensory block with 40 mg 2-CP was 117 (74–168) and with 50 mg 2-CP was 148 (116–176) min. The duration of motor block with 40 mg 2-CP was 104 (60–150) and with 50 mg 2-CP was 134 (106–158) min. In terms of hemodynamic parameters and adverse effects, there was no statistically significant difference found between both groups. Conclusion: Our study revealed that 40 mg of 1% 2-CP produces a satisfactory surgical block for procedures lasting <90 min. When compared with 1% 2-CP 50 mg, it resulted in comparable onset of action, with significantly faster regression of the block, shorter time to ambulation.